2017
DOI: 10.1080/16066359.2017.1350654
|View full text |Cite
|
Sign up to set email alerts
|

Bartenders as street-level bureaucrats: theorizing server practices in the nighttime economy

Abstract: Most Western countries have laws that prohibit the serving of alcohol to intoxicated and underage patrons in nightlife venues such as pubs and nightclubs. Despite laws and the implementation of server training programs, several studies have shown that intoxicated patrons are still likely to be served. This think-piece article attempts to shed new light on the tendency among bartenders to overserve patrons. Based on a selective review of the literature, we argue that future research on bartenders is in need of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
0
3
0
3
Order By: Relevance
“…Experience from Sweden of collecting data from this group of staff suggested that using a postal survey would result in a low response rate [18]. Staff at drinking establishments can be hard to reach [20], and there are no comprehensive registers of individuals employed at licensed premises. In addition, few of them are members of unions, and staff turnover is high [18, 21].…”
Section: Methodsmentioning
confidence: 99%
“…Experience from Sweden of collecting data from this group of staff suggested that using a postal survey would result in a low response rate [18]. Staff at drinking establishments can be hard to reach [20], and there are no comprehensive registers of individuals employed at licensed premises. In addition, few of them are members of unions, and staff turnover is high [18, 21].…”
Section: Methodsmentioning
confidence: 99%
“…Mens andre studier har vist hvordan bartendere kan være under press fra ledelsen for å selge mye alkohol ( Buvik & Tutenges 2017 ), fortalte bartenderne i denne studien at det manglende kravet om mersalg gjorde at salgssituasjonen opplevdes som friere. At Norge i utgangspunktet har en streng alkohollov som forbyr alkoholreklame og tilbud på alkohol, kan gjøre at norske bartendere i mindre grad enn internasjonale kolleger opplever dette presset.…”
Section: Diskusjonunclassified
“…En hovedvekt av bartenderstudier er kvantitative og fokuserer på problemorienterte forhold (Buvik & Tutenges, 2017). Studiene fokuserer i hovedsak på negative forhold som overskjenking (Buvik, 2013;Buvik & Rossow, 2015;Goodsite, Klear, & Rosenberg, 2008;Leo, 2013;Reiling & Nusbaumer, 2006), seksuelle overgrep og trakassering (Bråten & Øistad, 2017;Graham et al, 2014;Powers & Leili, 2016), bartenderes høye alkoholkonsum og illegale rusbruk (Buvik, Bye, & Gripenberg, 2018;Kjaerheim & Mykletun, 1995;Larsen, 1994;Norström, Sundin, Müller, & Leifman, 2012) eller bartenderes rolle på utesteder med mye vold (Graham & Homel, 2008;Hobbs, Hadfield, Lister, & Winlow, 2002).…”
unclassified
See 1 more Smart Citation
“…When a bartender checks patron I.D. 's to ensure that they are old enough to drink (Buvik & Tutenges, 2018), or an exotic dancer polices the physical conduct of clientele (Price-Glynn, 2010), the state has essentially deputized a nongovernment actor to ensure that the spirit of a sumptuary law is carried out. This partnership is also the bedrock for a unique form of decoupling, one that pits the intention of policies to restrain problematic consumption against the motivation to maximize revenues.…”
Section: Introductionmentioning
confidence: 99%